2021
DOI: 10.1101/2021.11.06.21266005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many Oil Wells, One Evil: Potentially toxic metals concentration, seasonal variation and Human Health Risk Assessment in Drinking Water Quality in Ebocha-Obrikom Oil and Gas Area of Rivers State, Nigeria

Abstract: BackgroundOil and natural gas extraction have produced environmental pollution at levels that affect reproductive health of indigenous populations. Accordingly, polluted drinking water from physical, chemical and heavy metals can result in serious health problems, like anemia, kidney failure, immunosuppression, neurological impairments, gastrointestinal as well as respiratory irritation, skeletal system abnormalities, liver inflammation, liver cancer, cardiovascular diseases after chronic exposure and other ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 92 publications
(395 reference statements)
0
39
0
Order By: Relevance
“…Because groundwater is a key supply of water for human consumption, its low quality can have substantial consequences [1,2,3,4,5,6,7,8]. While groundwater is traded in some regions of the world, it is also widely used as a supply of water for home, industrial, agricultural, and energy generation operations [9,10,11,12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because groundwater is a key supply of water for human consumption, its low quality can have substantial consequences [1,2,3,4,5,6,7,8]. While groundwater is traded in some regions of the world, it is also widely used as a supply of water for home, industrial, agricultural, and energy generation operations [9,10,11,12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…While groundwater is traded in some regions of the world, it is also widely used as a supply of water for home, industrial, agricultural, and energy generation operations [9,10,11,12,13,14,15,16,17,18,19,20,21]. Humans need water and water is at the core of sustainable development' [7,8,21,22,23,24,25,26,27]. Water resources, and the services they supply, are critical to economic growth, poverty alleviation, and environmental sustainability [5,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors claimed that humankind is heading beyond a "safe operating area" as the size of these consequences approaches or exceeds certain thresholds that indicate global system tipping points or natural limits for processes with no apparent limits (so-called "hazardous levels"). Numerous researchers have reported that human health is generally influenced by their environment (Ecological Security Organization (EPA), 2015), Raimi and Sabinus, 2017;Olalekan et al, 2018;Suleiman et al, 2019;Raimi et al, 2019a;Raimi et al, 2019b;Raimi et al, 2019c;Olalekan et al, 2019;Okoyen et al, 2020;Adedoyin et al, 2020;Olalekan et al, 2020a;Olalekan et al, 2020b;Olalekan et al, 2020c;Raimi et al, 2021a;Raimi et al, 2021b;Raimi et al, 2021c;Morufu et al, 2021a;Morufu et al, 2021b;Morufu et al, 2021c;Morufu et al, 2021d;Morufu et al, 2021e) and specifically, the nature and quality of the food (Ames, 1983;Oluwaseun et al, 2019;Afolabi and Raimi, 2021). Nature cattle products is broadly concerning public health body throughout the globe since veterinary medications have assumed a significant part in the field of animal farming and agro-industry, and increasing event of drug residues, and resistance have become issues of concern (Rokka et al, 2005).…”
mentioning
confidence: 99%